98.1k views
5 votes
4x^2-15x-4

factorise please ​

1 Answer

6 votes

Answer:


\boxed{4x^2-15x-4=(x-4)(4x+1)}

Solution Steps:

______________________________

1.) Change the equation using factored transformation:


  • 4x^2-15x-4=0

- Quadratic polynomial can be factored using the transformation
ax^2+bx+c=a(x-x_(1))(x-x_(2)), where
x_(1) and
x_(2) are the solutions of the quadratic equation
ax^2+bx+c=0.

- This steps basically means change you current equation using the formula
ax^2+bx+c=0.

2.) Turn the factored form into the quadratic equation form:


  • x=\frac{-(-15)\frac{+}{}\sqrt{(-15)^2-4\bold{x}4(-4)}}{2\bold{x}4}

- All equations of the form
ax^2+bx+c=0 can be solved using the quadratic formula:
\sqrt{\frac{-b\frac{+}{}√(b^2-4ac)}{2a} }.

- The quadratic equation formula gives two solutions, one when
\frac{+}{} is addition and one when it is subtraction.

3.) Square -15:


  • -15^2=225

Equation at the end of Step 3:


  • x=\frac{-(-15)\frac{+}{}\sqrt{225-4\bold{x}4(-4)}}{2\bold{x}4}

4.) Multiply −4 times 4:


  • -4 ×
    4=-16

Equation at the end of Step 4:


  • x=\frac{-(-15)\frac{+}{}√(225-16(-4))}{2\bold{x}4}

5.) Multiply −16 times −4:


  • -16 ×
    -4=64

Equation at the end of Step 5:


  • x=\frac{-(-15)\frac{+}{}√(225+64)}{2\bold{x}4}

6.) Add 225 to 64:


  • 225+64=289

Equation at the end of Step 6:


  • x=\frac{-(-15)\frac{+}{}√(289)}{2\bold{x}4}

7.) Take the square root of 289:


  • √(289)=17

Equation at the end of Step 7:


  • x=\frac{-(-15)\frac{+}{}17}{2\bold{x}4}

8.) Change -15 to positive 15:


  • -15=15

Equation at the end of Step 8:


  • x=\frac{15\frac{+}{}17}{2\bold{x}4}

9.) Multiply 2 by 4:


  • 2 ×
    4=8

Equation at the end of Step 9:


  • x=\frac{15\frac{+}{}17}8}

10.) Now Solve:

Now solve the equation
x=\frac{15\frac{+}{}17}8} when
\frac{+}{} is plus.

Add 15 to 17:


  • 15+17=32

  • x=(32)/(8)

Divide 32 by 8:


  • 32 ÷
    8=4

  • x=4

Now solve the equation
x=\frac{15\frac{+}{}17}8} when
\frac{+}{} is minus.

Subtract 15 by 17:


  • 15-17=-2

  • x=(-2)/(8)

Reduce the fraction to lowest terms by extracting and canceling out 2:


  • -2 ÷
    -2=-1

  • 8 ÷
    -2=-4

  • x=-(1)/(4)

11.) Factor the expression:

Factor the original expression using
ax^2+bx+c=a(x-x_(1))(x-x_(2)). Substitute 4 for
x_(1) and
-(1)/(4) for
x_(2):


  • 4x^2-15x-4=4(x-4)(x-(-(1)/(4)))

Simplify all the expressions of the form
p-(-q) to
p+q:


  • 4x^2-15x-4=4(x-4)(x+(1)/(4))

Add
(1)/(4) to x by finding a common denominator and adding the numerators. Then reduce the fraction to lowest terms if possible:


  • 4x^2-15x-4=4(x-4)\bold{x}((4x+1)/(4))

Cancel out 4, the greatest common factor in 4 and 4:


  • 4x^2-15x-4=(x-4)(4x+1)

______________________________

User Madlymad
by
5.8k points